1995
DOI: 10.1172/jci118056
|View full text |Cite
|
Sign up to set email alerts
|

Secretory leukocyte protease inhibitor: a human saliva protein exhibiting anti-human immunodeficiency virus 1 activity in vitro.

Abstract: Infection of adherent primary monocytes with HIV-lBa.L is significantly suppressed in the presence of human saliva. By reverse transcriptase (RT) levels, saliva, although present for only 1 h during monocyte viral exposure, inhibited HIV-1 infectivity for 3 wk after infection, whereas human plasma and synovial fluid failed to inhibit HIV-1 infectivity. Antiviral activity was identified in the saliva soluble fraction, and to determine the factor (s) responsible, individual saliva proteins were examined. Of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
370
4
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(390 citation statements)
references
References 55 publications
12
370
4
4
Order By: Relevance
“…50 The mechanism through which SLPI exerts its anti-viral action was previously shown to involve a host cell molecule and not to target the virus itself and to occur early in the viral life cycle. 5,6 Finally, the architectural uniqueness of the crypt epithelium probably also contributes to HIV transmission vulnerability in the tonsil. In the area of the crypt, the epithelium is thinner and has multiple breaks that may provide portals of entry for the virus while creating a less accessible environment to the anti-viral components of saliva, including SLPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 The mechanism through which SLPI exerts its anti-viral action was previously shown to involve a host cell molecule and not to target the virus itself and to occur early in the viral life cycle. 5,6 Finally, the architectural uniqueness of the crypt epithelium probably also contributes to HIV transmission vulnerability in the tonsil. In the area of the crypt, the epithelium is thinner and has multiple breaks that may provide portals of entry for the virus while creating a less accessible environment to the anti-viral components of saliva, including SLPI.…”
Section: Discussionmentioning
confidence: 99%
“…The oral cavity is considered a relatively protected mucosal site where the innate host defense molecules of saliva are capable of neutralizing HIV and the epithelium itself is not receptive for transmission. [3][4][5][6][7][8] Orogenital transmission has a very low per-contact risk of acquiring infection, with estimates that 4 of 10,000 contacts result in infection compared with heterosexual or homosexual genital contact (1 of 200 to 1000). 9 -12 Vertical transmission from mother to infant during breast feeding also occurs with varying rates but may be as high as 15% when breast-feeding is prolonged.…”
mentioning
confidence: 99%
“…Further investigation revealed that macrophages and neutrophils are rich sources of SLPI, and SLPI has been recognized to have antibacterial, antiviral, and antiinflammatory properties. These include the prevention of HIV replication in monocytic cells (12,13), the down-regulation of prostaglandin, and matrix metalloprotease synthesis by monocytes (14), and the inhibition of inflammatory lung injury caused by deposition of IgG-immune complexes (15), or of joint damage caused by bacterial cell wall-induced arthritis (16). We have previously found that serum SLPI is elevated in human sepsis and experimental endotoxemia (17), and that SLPI expression in murine macrophages is induced by LPS and lipotechoic acid (18,19) but suppressed by IFN-␥ (18).…”
mentioning
confidence: 99%
“…Its abundance in the upper respiratory tract suggests that the primary role of SLPI is to provide an anti-Neutrophil Elastase (anti-NE) shield for the tracheobronchial tree (Fryksmark et al, 1982, Mooren et al, 1983. SLPI has also been found to possess anti-bacterial, anti-viral and antiinflammatory activity including the ability to reduce nuclear factor-B (NF-B) activation intracellularly (Greene et al, 2004, Jin et al, 1997, Lentsch et al, 1999, McNeely et al, 1995, Taggart et al, 2002, Zhang et al, 1997. rSLPI is therefore a highly promising therapeutic for inflammatory lung disease.…”
Section: Introductionmentioning
confidence: 99%